PENERAPAN DISKRESI PEJABAT FUNGSIONAL PENGELOLA PENGADAAN BARANG/JASA DALAM PENYELENGGARAAN PENGADAAN BARANG/JASA PEMERINTAH - Vieka Ariestyani Antari; Mohammad Saleh (Jurnal HUKUM BISNIS, 2023)
This paper aims to determine the limits of the implementation of the discretion of the Goods/Services Procurement Management Functional Officer in the implementation of the Government's procurement of goods/services and to find out the form of legal protection for the Goods/Services Procurement Management Functional Officer for the application of discretion in the implementation of the Government's procurement of goods/services. The research method uses normative legal research, using the approach used in this study is the statutory approach and the conceptual approach. The focus of this research plan is the freedom to act on the basis of discretion exercised by government administration bodies/officials, not without limits. This freedom is limited by the General Principles of Good Governance (AAUPB), so it is hoped that there will be no abuse of authority. But if there is a legal deviation from the discretionary decision which results in losses to the community, then the discretionary decision must still be accounted for. By giving freedom of action (discretion) to the state administration in carrying out its duties to create a welfare state, it is hoped that public welfare will truly be created. Because in principle government administration agencies/officials may not refuse to provide services to the community on the grounds that the law does not exist or the law exists but is not clear, as long as this is still under their authority.Keywords: Discretion, Procurement of goods/services, Functional Position of Goods/Services Procurement Management